Autoimmune Diseases and Rates of Thromboembolism in Pregnancy [A278]. (May 2022) - Brewerton, Charles; Thomas, Jacob; Harrison, Rachel; Holmgren, Calla
Abstract : INTRODUCTION: Antiphospholipid syndrome (APLS) is associated with an increased risk of thromboembolism during pregnancy. Other autoimmune diseases are less well-studied. Given the pro-inflammatory state associated with these conditions, we sought to identify the risk of thromboembolic disease in pregnant patients with autoimmune conditions. METHODS: This is a retrospective cohort study utilizing the National Inpatient Sample (Healthcare Cost and Utilization Project) for the year 2018. Subjects were excluded if they had a history of thrombosis, inherited thrombophilia, or APLS. Patients with at least one autoimmune condition (rheumatoid arthritis, Type 1 diabetes, systemic lupus erythematosus, myositis, ulcerative colitis, Crohn's, Sjogren's, scleroderma, and Hashimoto's thyroiditis) were compared to unaffected pregnancies. The primary outcome was a composite of thrombotic events. Secondary outcomes included individual components of the composite including deep vein thrombosis, PE, arterial embolism, and cerebrovascular thrombosis. The groups were compared via Student's t-tests, Chi-square, and logistic regression analyses. RESULTS: The control cohort comprised 750, 743 pregnancies. The study cohort had 8, 605 patients with≥1 autoimmune condition. The patients with autoimmune conditions were more likely to be older, White, obese, chronic hypertensive, tobacco users, privately insured, and in the upper quartile of household income (all P <.001). After controlling for confounders that differed between groups with P <.05, presence of an autoimmune disease was independently associated with higher rates of thrombosis and embolic events, with rates of 0.6% compared to 0.2% in controls (aOR 2.40, 95%CI 1.75–3.28). CONCLUSION: Autoimmune disease is associated with an increased risk of thromboembolic disease in pregnancy.